SPECIAL URGENCY AND EMERGENCY SLAUGHTER: MANAGEMENT OF HEALTH PROBLEMS (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
The Authors take account of the difference between special urgency slaughter and emergency slaughter as well as of the management of the bovine animals and bovine carcasses, from culling on farm to the entry into the slaughterhouse. The Authors highlight the various and multiple health problems associated with this type of slaughter.